ОЦІНКА МОДЕРНІЗАЦІЙНОГО ПОТЕНЦІАЛУ ПІДПРИЄМНИЦТВА НА ОСНОВІ ДИНАМІЧНИХ ПОКАЗНИКІВ ДОДАНОЇ ВАРТОСТІ ВИСОКОТЕХНОЛОГІЧНОЇ ПРОДУКЦІЇ - Horiashchenko, Yuliia (Zhytomyr Ivan Franko State University, 2022)
The research is devoted to assessing the modernization potential of entrepreneurship based on indicators of value added of high-tech products. Firstly, the dynamics of value added costs for the production of enterprises in such economic activities as ICT, production using high, medium, low levels, information sector, services using high technology, services related to the use of computer intellectual market techniques and services. A parallel is drawn between innovative modernization and digital transformation. The conducted content analysis gave grounds to define innovative modernization of entrepreneurship as a continuous chain process of triage of the most valuable ideas, implementation of innovation results and obtaining the desired KPI, carried out under certain conditions. Such conditions include: established processes of cooperation between entrepreneurs, government, universities, corporations; access to human and financial capital; access to customers and consumers (new digital scalable products and services); speed of change of competitors. A matrix of business models in increasing gross value added, respectively, through the formation of the value chain, vertical integration (B2B), improving the characteristics of goods and services (B2C), expanding the range of sources and factors of gross value added (fiscal component of VAT, business support). manufacturing and exporting high-tech products (C2C), etc.